2004
DOI: 10.1128/jcm.42.11.4937-4946.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Putative Adhesins in Different Seropathotypes of Shiga Toxin-Producing Escherichia coli

Abstract: . The most prevalent adhesin was that encoded by the iha gene (91%; 127 of 139 strains), which was distributed in all seropathotypes. toxB and efa1 were present mainly in strains of seropathotypes A and B, which were LEE positive. saa was present only in strains of seropathotypes C, D, and E, which were LEE negative. Two fimbrial genes, lpfA O157/OI-141 and lpfA O157/OI-154 , were strongly associated with seropathotype A. The fimbrial gene lpfA O113 was present in all seropathotypes except for seropathotype A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

23
121
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(152 citation statements)
references
References 44 publications
(60 reference statements)
23
121
1
2
Order By: Relevance
“…The results of the present study indicate a large prevalence of iha gene in STEC strains irrespective of their origin (97% in human isolates and 94% in cattle isolates). Toma et al [37] suggested that Iha could be a candidate for vaccine development of STEC because of its wide distribution in STEC strains isolated in Argentina, Brazil and Japan (127 of 139 strains, 91%; Tables 2 and 3). In our study, however, ehaA gene was most prevalent in STEC strains regardless of serotype, origin and presence of LEE (98% and 95% in human and cattle isolates, respectively), indicating that EhaA might be the best candidate for vaccine development against STEC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present study indicate a large prevalence of iha gene in STEC strains irrespective of their origin (97% in human isolates and 94% in cattle isolates). Toma et al [37] suggested that Iha could be a candidate for vaccine development of STEC because of its wide distribution in STEC strains isolated in Argentina, Brazil and Japan (127 of 139 strains, 91%; Tables 2 and 3). In our study, however, ehaA gene was most prevalent in STEC strains regardless of serotype, origin and presence of LEE (98% and 95% in human and cattle isolates, respectively), indicating that EhaA might be the best candidate for vaccine development against STEC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genes encoding cytolethal distending toxin (CDT) [13] and subtilase cytotoxin (SubAB) [28] have also been identified in LEE-positive and LEE-negative STEC strains, respectively. Although the prevalence of genes encoding putative adhesins and newly identified toxins have been reported in STEC strains isolated from a limited geographic area [4,15,29,37], very little is known about the distribution of such virulence-related genes in STEC strains isolated in Japan.…”
mentioning
confidence: 99%
“…iha is present in 25 of 25 O157:H7 isolates of diverse origins but in only 3 of 20 commensal non-O157 fecal E. coli [8]. Additionally, iha is conserved among EHEC of a variety of serotypes [10]. Interestingly, an iha homologue is present on an island located at selC (where LEE is generally integrated into the chromosome) of LEE-negative STEC that produce activatable Stx2d [11].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, gene lpfA O157/OI154 was the most frequent gene detected, being found significantly among pathogenic strains, including all swollen head syndrome (P = 0.00001), omphalitis (P = 0.00001) and septicemia strains (P = 0.005). Gene lpfA O157/ OI154 is one of the four genetic variants of lfpA gene identified in STEC (Toma et al, 2004) and in other diarrheagenic E. coli strains (Toma et al 2006). The lpfA encodes for the variants of the long polar fimbriae (LPF) that are adhesins related to Type 1 fimbriae, first identified in Salmonella enterica serovar Typhimurium (Bäumler et al 1995).…”
Section: Discussionmentioning
confidence: 99%